Revisiting the Finance-Environment Nexus: The Joint Role of Remittances and FDI in Sustainable Development - Serfraz, Ayesha; Qamruzzaman, Md (International Journal of Energy Economics and Policy, 2026)
This study examines the influence of remittances, imports, household consumption, renewable energy consumption, financial development, globalization, and institutional quality on environmental sustainability in major remittance-receiving economies. Environmental degradation is assessed through CO₂ emissions and the ecological footprint, allowing for a comprehensive evaluation of both emission intensity and ecological pressures. Utilizing annual data and advanced panel econometric methods, this analysis addresses cross-sectional dependence, slope heterogeneity, persistence, and endogeneity. The empirical framework integrates Cross-Sectionally Augmented ARDL (CS-ARDL) for baseline long- and short-run dynamics, robustness checks using Common Correlated Effects Mean Group (CCEMG) and Augmented Mean Group (AMG), dynamic Generalized Method of Moments (GMM) estimators, and asymmetric nonlinear ARDL specifications. Additionally, Panel Quantile Regression with Method of Moments (PQR-MM) was employed to capture heterogeneous effects across the distribution of environmental outcomes. The results indicate that remittances contribute to environmental improvements, although the magnitude varies between positive and negative shocks, confirming asymmetric effects. Renewable energy consumption consistently mitigates environmental degradation across specifications. Conversely, imports, household consumption, financial development, and globalization exacerbate ecological pressures, whereas institutional quality plays a crucial moderating role in reducing adverse environmental impacts. The quantile estimates reveal the stronger effects of remittances, renewable energy, and governance at higher levels of environmental stress, emphasising the importance of policy targeting in heavily affected economies. These findings underscore the interplay between financial flow, governance, and energy use in global sustainability. This study contributes to the literature on globalization by illustrating how remittances and institutional frameworks can transform global integration and financial expansion into opportunities for ecological resilience, aligned with international climate and development agendas.